Test for Bacterial Content in Soy Sauce and Tomato Sauce at Masomba Market, Palu City - Hasrina (Journal of Public Health and Pharmacy)
The development of industrial food products that are growing rapidly and are ready-to-eat, make people increasingly fond of complementary food products, namely sauces and soy sauce. Even the food consumed is of particular concern because it causes many losses, such as patients who are poisoned or whose digestion is disrupted due to the food being consumed has been contaminated by materials or microorganisms. This study aims to determine the bacterial content of various brands of soy sauce and tomato sauce in Masomba market, Palu City. The method used in this research is descriptive research using an observational approach where in practice this study aims to determine the presence or absence of bacteria in soy sauce and tomato sauce of various brands in Masomba Palu market. Based on the results of research conducted on ten samples of soy sauce and tomato sauce sold at the Masomba market in Palu which was carried out at the Environmental Health Laboratory of Poltekkes, the Ministry of Health, Palu, it was found that one positive sample contained Eschercia coli and Staphlococcus bacteria, namely the soy sauce sample E with MPN number 43, and Staphlococcus. aureus with 12 colonies. This study suggests that soy sauce producers should increase the selection of good raw materials and improve the sanitation of soy sauce making. For the community, it is expected to be more careful in choosing the soy sauce snacks that will be consumed. For further researchers, it is hoped that they will be able to examine other pathogenic bacteria and check the content of other food additives contained in soy sauce such as preservatives, thickeners.